Red fox immune-gene SNPs - Donaldson, Michael E.; Rico, Yessica; Hueffer, Karsten; Rando, Halie M.; Kukekova, Anna V.; Kyle, Christopher J. (Dryad Digital Repository, 2017)
Red fox SNP variant call information.